2020
DOI: 10.1210/clinem/dgaa150
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and Folate Concentrations in Recent-onset Type 2 Diabetes and the Effect of Metformin Treatment

Abstract: Context Vitamin B12 and folate deficiency are not only linked to hematological, neurological, and cardiovascular diseases, but are also associated with insulin resistance. Metformin can decrease vitamin B12 and folate concentrations. Objective To examine (1) effects of short-term metformin treatment on serum holotranscobalamin (holoTC) and folate and (2) their association with insulin sensitivity in recent-onset type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
6
1
1
Order By: Relevance
“…As previously noted, we observe significant negative age associations with vitamin B 6 , but none with vitamin B 12 . Given that folate is almost always nontoxic to humans, folate deficiency has been the frequent culprit in disease processes including those that are age-related like diabetes and cataracts (40,41). Our observed positive association of folate with GrimAge and PhenoAge seems contrary to this relationship, but the literature contains similar paradoxical folate relationships with other aging markers like mitochondrial DNA copy number and telomere length (42,43).…”
Section: Discussionmentioning
confidence: 48%
“…As previously noted, we observe significant negative age associations with vitamin B 6 , but none with vitamin B 12 . Given that folate is almost always nontoxic to humans, folate deficiency has been the frequent culprit in disease processes including those that are age-related like diabetes and cataracts (40,41). Our observed positive association of folate with GrimAge and PhenoAge seems contrary to this relationship, but the literature contains similar paradoxical folate relationships with other aging markers like mitochondrial DNA copy number and telomere length (42,43).…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, metformin therapy has been reported to decrease serum levels of vitamin B12, and long-term use of metformin is associated with vitamin B12 deficiency. However, metformin does not affect circulating concentrations of vitamin B12 and folic acid at least during the first 6 mo after initiating (30,31). In our study, over half of total subjects were metformin users, but the average of serum vitamin B12 concentrations was within normal ranges.…”
Section: Discussioncontrasting
confidence: 49%
“…Of these, 15 (62.5 %) were female and 9 (37.5 %) were male. The mean age of patients was 13.7 ± 2.3 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years. Sixteen patients were diagnosed with metabolic syndrome, and 8 patients suffered from type-2 DM.…”
Section: Resultsmentioning
confidence: 99%
“…The study, including 700 adult patients, found that holo-TC-II was the best marker of vitamin B12 deficiency 28 . A cross-sectional analysis reported by Kanti et al includes a large study population with diabetes mellitus (123 patients treated with metformin for at least 6 months; and 126 patients with nonpharmacological treatment) which showed that holo-TC-II and cobalamin levels were similar in both groups 18 . However, another study observed no decrease in holo-TC-II levels, while a significant decrease was detected in vitamin B12 levels in patients diagnosed with PCOS 14 .…”
Section: Discussionmentioning
confidence: 99%